KOMUNITAS VIRTUAL IIDN (IBU-IBU DOYAN NULIS) - Amelia, Vita (Jurnal Ilmu Budaya, 2015)
In cyber technology era, the existence of virtual community isunavoid able phenomenon. It has changed real world activities to cyberworld. Consequently, everything done in the real world can be found in qber world. Related to that idea, this writing deals with virtual community which involves women who interact in cyber world. They are encouraged and trained to write well. This phenomenon is interesting since women, particularly housewives are given chance to sharpen their writing ability so that they can write good writings and publish them.